Assessment of Proximate and Mineral Composition of Sesame Seed (Sesamum indicum linn) Grown in Kashere - T. S. Tyohemba; S. M. Ladan; N. N. Ndukwe; C. O. Attah; A. Jummai; G. G. Memi; S.Z., Na’inna; A, Mamoon; S.W Kopdorah (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This research paper employs standard procedures to analyse the proximate and mineral composition of Sesamum indicum seeds grown in Kashere. Proximate analysis results revealed moisture content of 6.89±0.014%, total ash of 5.79±0.021%, crude fibre of 6.69±0.021%, crude protein of 18.43±0.11% and carbohydrate of 19.72±0.16%. The mineral analysis showed that Sesamum indicum seeds grown in Kashere contain significant amounts of sodium (29.50±0.707 mg/100g), potassium (113.55±0.495 mg/100g), calcium (249.80±0.424 mg/100g), magnesium (2.98±0.035 mg/100g), and iron (2.88±0.035 mg/100g). Therefore, these seeds can be considered a excellent source of essential nutrients, minerals, and crude fibre. The significant amounts of crude protein and carbohydrate make them a valuable source of nutrition for humans and animals, and their total ash and crude fibre content suggest potential as an ingredient in the food industry. The significant presence of vital minerals, including calcium and phosphorus, found in Sesamum indicum seeds grown in Kashere can help improve bone health. The study’s results provide valuable information concerning the nutritional value of sesame seeds. These findings can support the supplementary use of sesame seeds in human and animal nutrition as well as their inclusion in the food industry.